Outlining the Issues of Cloud Computing and Sustainability Opportunities and Risks in European Organizations: A SEM Study - Isaias, P.; Issa, Tomayess; Chang, V.; Issa, Theodora (IGI Global Publishing, 2015)
Cloud computing and sustainability have become part of a core strategy in organizations globally and locally, since their characteristics assist both businesses and individuals to become unique and exclusive in their work and study. Businesses and individuals should integrate sustainability in their strategy and to include cloud computing technology as a tool for sustainable work, especially in the Information Technology (IT) departments to cut costs and increase efficiencies and productivity. This paper examines European organizations' awareness of cloud computing and sustainability opportunities and risks, via an online survey targeting 56 Information Technology managers in Europe. A Cloud Computing Conceptual model was developed using structural equation modeling (SEM) to evaluate the survey results. The study results confirmed that cloud computing technology opportunities, including sustainability in the organization's strategy, will enhance their job performance and job satisfaction, use and awareness; however, security, privacy and risks are still a major concern.